2018
DOI: 10.1038/s41366-018-0270-3
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms, perceived stress, and metabolic health: The REGARDS study

Abstract: Objective: To describe the relationship between metabolic health parameters and depressive symptoms and perceived stress, and whether the co-occurrence of these two psychological stressors has an additive influence on metabolic dysregulation in adults at different levels of body mass index (BMI) without diabetes. Methods: Participants without diabetes (N=20,312) from the population-based REasons for Geographic And Racial Differences in Stroke (REGARDS) study (recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 45 publications
1
26
0
1
Order By: Relevance
“…What's more, referring to perceived stress, Shelef et al reported that perceived stress was identified as one of primary determinants among young suicide attempters [45]. And Gowey MA reported that increased depressive symptoms and perceived stress are usually associated with decreased level of HDL [46]. So, we considered that a certain degree of perceived stress may take part in the influence of lower HDL-C on suicide attempts.…”
Section: Discussionmentioning
confidence: 89%
“…What's more, referring to perceived stress, Shelef et al reported that perceived stress was identified as one of primary determinants among young suicide attempters [45]. And Gowey MA reported that increased depressive symptoms and perceived stress are usually associated with decreased level of HDL [46]. So, we considered that a certain degree of perceived stress may take part in the influence of lower HDL-C on suicide attempts.…”
Section: Discussionmentioning
confidence: 89%
“…Elevated stress was defined as a score on the 4-item Perceived Stress Scale of 8 or greater. 52 Social support was assessed using self-reported marital status and the presence or absence of a social network, defined as a report of having seen either no friends or relatives or only 1 friend or relative in the past month. 53 Additional caregiver characteristics were also collected; participants who responded affirmatively to being caregivers were asked about their social support system and (1) whether they lived with the care recipient, (2) how this person was related to them (eg, spouse, parent), and (3) how many hours per week they spent providing care to this person (<10, 10-19, 20-29, or >30 hours).…”
Section: Methodsmentioning
confidence: 99%
“…FS-affected individuals demonstrate obsessive personality and tendency to perfectionism frequently linked to increased psychologic stress [170] that has been extensively discussed in context of several pathologies potentially linked to FS phenotype including both neurodegenerative eye disorders [179] and oncologic diseases [152][153][154], and corresponding molecular mechanisms and targets for response have been clearly identified [180,181]. Similarly, chronic stress and mood disorders have been proposed to play significant role in the pathomechanisms of the multifactorial stroke predisposition [182,183].…”
Section: Psychologic Factors and Stressmentioning
confidence: 99%